2010
DOI: 10.1037/a0018389
|View full text |Cite
|
Sign up to set email alerts
|

Loudness change in response to dynamic acoustic intensity.

Abstract: Three experiments investigate psychological, methodological, and domain-specific characteristics of loudness change in response to sounds that continuously increase in intensity (up-ramps), relative to sounds that decrease (down-ramps). Timbre (vowel, violin), layer (monotone, chord), and duration (1.8 s, 3.6 s) were manipulated in Experiment 1. Participants judged global loudness change between pairs of spectrally identical up-ramps and down-ramps. It was hypothesized that loudness change is overestimated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 49 publications
5
36
1
Order By: Relevance
“…Such studies could also investigate the role of time-reversing speech signals on their loudness in more detail. Ratings of global loudness and loudness change measured with ramped and damped stimuli (i.e., with stimuli comprising aslowonset and asharp offset or vice versa)showed an increased loudness for ramped compared to damped stimuli [45,46,47], butsee also [48,49]. In this light, one could expect that time-reversed speech should be slightly louder than unprocessed speech because its temporal envelope is more similar to ramped stimuli (see [50,51]).…”
Section: Factors Affecting Loudness Of Speechmentioning
confidence: 98%
“…Such studies could also investigate the role of time-reversing speech signals on their loudness in more detail. Ratings of global loudness and loudness change measured with ramped and damped stimuli (i.e., with stimuli comprising aslowonset and asharp offset or vice versa)showed an increased loudness for ramped compared to damped stimuli [45,46,47], butsee also [48,49]. In this light, one could expect that time-reversed speech should be slightly louder than unprocessed speech because its temporal envelope is more similar to ramped stimuli (see [50,51]).…”
Section: Factors Affecting Loudness Of Speechmentioning
confidence: 98%
“…The dynamic range scale was intended to measure whether listeners are sensitive to the changes in dynamic range caused by DRC. In this study, dynamic range was defined as "loudness changes," as described previously by Neuhoff (2001) and Olsen et al (2010). Pleasantness and preference scales were included separately due to the possibility that a listener may judge a particular musical sound as less pleasant, but may still prefer that sound (e.g., distortion on an electric guitar).…”
Section: B Sound Quality and Loudnessmentioning
confidence: 99%
“…In particular, it has been found that sounds increasing in level over time-also referred to as up-ramps-are perceived as louder (Susini et al, 2007) or changing more in loudness (Neuhoff, 1998;Olsen et al, 2010) than sounds decreasing over time-also referred to as down-ramps. Though several hypotheses have been proposed, the causes of these findings, involving perceptual phenomena specifically related to time-varying sounds, are still not clearly identified (e.g., Pastore and Flint, 2011).…”
Section: Introductionmentioning
confidence: 99%